2021
DOI: 10.1155/2021/8819884
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells from Human Exfoliated Deciduous Teeth Attenuate Trigeminal Neuralgia in Rats

Abstract: Trigeminal neuralgia is an incurable progressive nervous system disease that can last for several months or years. Stem cells from human exfoliated deciduous teeth (SHED) are a candidate source for cell-based therapy. Owing to their neuroprotective and immunomodulatory effects, these neural crest cells have potential roles in mediating chronic pain. In this study, we established a rat model of chronic constriction injury of the infraorbital nerve (CCI-ION) to evaluate the analgesic effect of SHED in neuropathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Consistent with the present observations, a single intraspinal administration of SHED-CM loaded in collagen hydrogel showed anti-allodynic effects in the spinal cord injury model in rats 12 . In addition, the mean head withdrawal threshold in rats with infraorbital nerve ligation was significantly increased by a single systemic or local injection of SHED 20 . Accordingly, SHED has a potential therapeutic effect on severe neuropathic pain in animals.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Consistent with the present observations, a single intraspinal administration of SHED-CM loaded in collagen hydrogel showed anti-allodynic effects in the spinal cord injury model in rats 12 . In addition, the mean head withdrawal threshold in rats with infraorbital nerve ligation was significantly increased by a single systemic or local injection of SHED 20 . Accordingly, SHED has a potential therapeutic effect on severe neuropathic pain in animals.…”
Section: Discussionmentioning
confidence: 94%
“…However, 6-CFDA-labeled SHED selectively migrated in the damaged site but not in the intact site, and anti-allodynic effects of SHED lasted for 20 days. After SHED administration, SHED migrated into the injured but not the intact side of the trigeminal ganglion after infraorbital nerve injury (a model of orofacial neuropathic pain) in rats 20 . Furthermore, the anti-allodynic effects of SHED lasted for 8 weeks 20 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the neurogenic differentiation in vivo and neural crest origin of SHED, they provide an alternative model for treating chronic pain, including TN. We previously showed that SHED are crucially involved in attenuating TN; however, the underlying mechanisms remain unclear (Bai et al 2021b).…”
Section: Introductionmentioning
confidence: 99%